Legislation and Lifelong Learning in Canada: Inconsistencies in Implementation - Rollings-Magnusson, Sandra (Canadian Journal of Higher Education, 2001)
Governments in Canada at both the federal and provincial levels indicate that they support the policy of enhancing education to increase the 'intellectual capital' of the Canadian workforce as they believe that this would in turn, improve the economy. The lifelong learning agenda is at the heart of this effort. However, it is argued in this article that a review of government policy as expressed in legislation reveals inconsistencies between rhetorical and actual statutory support for the life- long learning agenda. The absence of the protection and sense of permanence that legislation provides to policy implementation means that any actions taken or programs created may be easily changed, ignored or eliminated with little public scrutiny or debate. Further, this absence establishes a lack of firm ongoing political commitment to achieving the learning agenda.